Analysis of Compensation and Work Environment on Employee Productivity in Regional Water Drinking Companies, Lumajang District. - Fauzan Muttaqien; Imam Abrori; Retno Cahyaningati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
Employee work productivity can grow if there is reasonable compensation and a conducive work environment (Muttaqien, 2019) . If desires, wishes and policies are balanced and realistic, they will have a positive impact on work productivity. Therefore the quality of human resources is a very vital factor in its role in supporting the company's productivity to achieve its goals (Muttaqien, 2021) . From the phenomenon of several companies that have not been able to provide compensation and a good work environment, it will have an impact on decreasing work productivity. The regional drinking water company (PDAM) of Lumajang Regency is a public sector company (BUMD) which has quite large assets and has a very large number of customers. the product is in the form of clean water that is suitable for consumption so it is worthy of research. This study describes the relationship between independent and dependent variables ( explanatory research ) . The aim is to determine the significance of the effect of the compensation variable and work environment variables on employee work productivity PDAM Lumajang. The results of the study of 45 respondents show that the effect of compensation and work environment is significant on the work productivity of employees at PDAM Lumajang. The results of the coefficient of determination show that 37% of employee productivity can be explained by compensation and work environment variables , while 63 % of employee productivity is influenced by other variables , such as motivation, leadership, communication and others.